Covid-19 and the impacts on mental health: a sample from Rio Grande do Sul, Brazil - Duarte, Michael de Quadros; Santo, Manuela Almeida da Silva; Lima, Carolina Palmeiro; Giordani, Jaqueline Portella; Trentini, Clarissa Marceli (Ciência & saude coletiva, 2020)
Pandemics such as that of COVID-19 affect a relatively large number of people and impose new rules and social habits on the world population. Information about the pandemic is constant in the media. Moreover, social distancing has been adopted in Brazil to prevent the spread of COVID-19, which may have economic and psychosocial consequences. This study aimed to verify the factors associated with indicators of mental disorders symptoms in residents of Rio Grande do Sul during the initial period of the social distancing policy. The study was approved by CONEP. There were 799 participants, aged between 18 and 75 years (M = 36.56; SD = 12.88); 82.7% were women, who answered a sociodemographic questionnaire of social distancing and the Self-Report Questionnaire (SRQ-20). The results indicated that having decreased income in the period, being part of the risk group and being more exposed to information about deaths and infected, are factors that can significantly harm mental health in this pandemic period. Investigating social determinants that contribute to greater vulnerability to the mental illness of the population is vital in the field of collective health for the planning of public actions and policies.